Formulation and Characterization of Isradipine Nanoparticle for Dissolution Enhancement - Rawaa M. Hussien; Mowafaq M. Ghareeb (College of Pharmacy University of Baghdad, 2021)
Isradipine belong to dihydropyridine (DHP) class of calcium channel blockers (CCBs). It is  used in the treatment of hypertension, angina pectoris, in addition to Parkinson disease. It goes under the BCS class II drug (low solubility-high permeability). The drug will experience extensive first-pass metabolism in liver, therefore, oral bio-availability will be approximately15 to 24 %.    The aim of this study was to formulate and optimize a stable  nanoparticles of a highly hydrophobic drug, isradipine by anti-solvent microprecipitation Method to achieve the higher in vitro dissolution rate, so that it will be absorbed by intestinal lymphatic transport in order to avoid hepatic first-pass metabolism  and improve drug bioavailability.   Twenty one formulas of Isradipine nanoparticles were prepared by antisolvent precipitation method utilizing one of these polymers (Poloxamer 188, PVP-k30, HPMC E5, PVA, Poloxamer 407, and Soluplus) at different drugs: polymer ratios. The polymer type, the drug to polymer ratio, ultrasonication power and the effect of addition of co-stabilizer on the particle size, and polydispersity index (PDI)  were investigated.   Among all the prepared nanoparticles formulas, formula (F9) which contain Soluplus as a stabilizer at polymer: drug ratio of (1:0.75) and solvent: antisolvent ratio of (1:9) was considered as the optimum formula which shows good evaluation parameters in addition to the increment in the solubility to about 10 times than that of the pure drug. The investigations of the drug-excipients compatibility studies by FTIR and DSC, crystalline state by P-XRD, surface morphology by SEM were done. Moreover, the analysis by DSC and SEM of the nanoparticles of the selected formula (F12) indicate a reduction in the crystallinity and amorphization of the drug. It can be concluded that the dissolution rate of Isradipine was significantly increased through particle size reduction to nanosize.